Conservation genetics of two island endemic Ribes spp. (Grossulariaceae) of Sardinia: survival or extinction?. (16th April 2015) - Gentili, R.; Fenu, G.; Mattana, E.; Citterio, S.; De Mattia, F.; Bacchetta, G.; Peeters, T.
Abstract Measuring levels of population genetic diversity is an important step for assessing the conservation status of rare or endangered plant species and implementing appropriate conservation strategies. Populations of Ribes multiflorum subsp. sandalioticum and R. sardoum, two endangered endemic species from Sardinia, representing the whole genus on the island, were investigated using ISSR and SSR markers to determine levels and structure of genetic variability in their natural populations. Results indicated medium to low genetic diversity at the population level: Nei's gene diversity for ISSR markers ranged from 0.0840 to 0.1316; the expected heterozygosity (HE) for SSR ranged from 0.4281 to 0.7012. In addition, only one remnant population of R. sardoum showed a high level of inbreeding, in accordance with its very small size. Regarding the structure of the six R. sandalioticum populations, both principal coordinates analysis (PCoA) and STRUCTURE analysis of ISSR and SSR data highlighted low population structure, although two populations appeared to be clearly distinct from the others. The genetic pattern of the two taxa associated with their different ecological positions indicated resilience of R. sandalioticum populations in fresh and humid habitats and uncertain future resistance for the residual R. sardoum population in xeric calcareous stands. Hence, this study highlights the importance of an integrated conservation approach (genetic plus in situ and ex situ conservation studies/measures) for activating management programmes in these endemic and threatened taxa that can be considered as crop wild relatives of cultivated Ribes species.